Rapid Pressureless Sintering of Glasses. Issue 17 (30th March 2022) - Lin, Zhiwei; Zhao, Xinpeng; Wang, Chengwei; Dong, Qi; Qian, Ji; Zhang, Guangran; Brozena, Alexandra H.; Wang, Xizheng; He, Shuaiming; Ping, Weiwei; Chen, Gang; Pei, Yong; et al.
Abstract: Silica glasses have wide applications in industrial fields due to their extraordinary properties, such as high transparency, low thermal expansion coefficient, and high hardness. However, current methods of fabricating silica glass generally require long thermal treatment time (up to hours) and complex setups, leading to high cost and slow manufacturing speed. Herein, to obtain high‐quality glasses using a facile and rapid method, an ultrafast high‐temperature sintering (UHS) technique is reported that requires no additional pressure. Using UHS, silica precursors can be densified in seconds due to the large heating rate (up to 10 2 K s −1 ) of closely placed carbon heaters. The typical sintering time is as short as ≈10 s, ≈1–3 orders of magnitude faster than other methods. The sintered glasses exhibit relative densities of > 98% and high visible transmittances of ≈90%. The powder‐based sintering process also allows rapid doping of metal ions to fabricate colored glasses. The UHS is further extended to sinter other functional glasses such as indium tin oxide (ITO)‐doped silica glass, and other transparent ceramics such as Gd‐doped yttrium aluminum garnet. This study demonstrates an UHS proof‐of‐concept for the rapid fabrication of high‐quality glass and opens an avenue toward rapid discovery of transparent materials. Abstract : A rapid pressureless sintering technique for sintering glasses is developed. The high heating rate and high sintering temperature dramatically reduce the sintering time from hours to seconds. The technique enables the sintering of glasses with different shapes, functional glasses, and transparent ceramics, which can be applied for discovering other advanced glass materials for advanced optics, optoelectronics, and energy‐efficient buildings.